Hadith And Technological Challenges In The Contemporary Era - Muhlis, Wachida; Hajar, Ibnu (Al-Bukhari : Jurnal Ilmu Hadis, 2023)
This research identifies the ways in which hadiths are interpreted and applied in the diverse social and cultural contexts of today in response to social and technological changes. The study outlines how religious education can adapt to technological advancements, the necessity of supervision and regulation to address ethical issues, and the importance of using technology as an effective tool for religious outreach. This research also underscores the importance of interfaith dialogue and an inclusive approach in understanding the role of hadiths in addressing technological challenges in the contemporary era. The research method employed is a qualitative approach, collecting data through literature studies and document analysis related to hadiths and technology usage. The collected data is thematically analyzed to identify trends, ethical issues, and the role of religious leaders in guiding the Muslim community in facing technological challenges. The research findings emphasize the need for religious education to adapt to technological developments, the necessity of supervision and regulation to address ethical issues, and the significance of utilizing technology as an effective tool for religious outreach.